Bagaimana Dampak Burnout pada Kinerja Konselor: Ditinjau dari Kode Etik Profesi - Maya Ningrat; Nadia Aulia Nadhirah; Nandang Budiman (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
The profession of a counselor has responsibilities and job demands that require you to remain professional in carrying out your duties. The large number of work demands that must be carried out by the counselor is the cause of burnout so that it can have an impact on the counselor’s performance. This study aims to identify the factors that cause burnout in counselors and the resulting impact seen from the counselor’s performance when carrying out their duties. The method used in this research is a systematic literature review (SLR) by presenting some of the results of previous research originating from journal articles on Google Scholar so that five relevant previous studies are obtained. Based on five previous studies, it was found that counselors are prone to experiencing burnout due to work demands factors related to different counselee problems and a lack of social support. Counselors who experience burnout are marked by feeling emotionally exhausted then experience a depersonalization stage and at the final stage are characterized by low self-esteem. The impact of burnout on counselor performance from several previous studies has shown a decrease in counselors even becoming unprofessional in providing services to counselees. This is not in accordance with the professional code of ethics regarding the principles of professionalism that must be possessed by counselors in carrying out their duties by respecting and providing the best service for counselees.